Study on the Significance and Pathways of Digital Technology Empowering Rural Public Services - Lang, Pengwu (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The key link in promoting rural digital construction lies in the empowerment of digital technology, which is also an important component of achieving digitalization of rural public services. Digital technology plays a crucial role in the digitization, precision, and intelligence of rural public services, effectively promoting the digitalization process of rural public services. At present, there are still objective problems in empowering rural public services with digital technology, such as incomplete digital infrastructure, insufficient digital talents, and incomplete data sharing mechanisms. It is necessary to strengthen rural infrastructure construction, accelerate the construction of digital technology talent teams for rural public services, build a data sharing mechanism for rural public services, promote the integration and development of digital technology and rural public services, and improve the level and efficiency of rural public services.